El riesgo percibido y la gestión de la seguridad - Rodríguez Garzón, Ignacio (2015)
Introduction: Firefighters are workers who usually live with risks inherent with their profession. Objectives: To delve about the concept of perceived risk as a tool for managing occupational risk. Materials and methods: The model used for risk quantification was the psychometric paradigm. Thus, anonymous surveys were conducted at different fire stations. The questionnaire contained demographic questions, nine questions on various attributes of risk and a question about risk perception of the subject in general. Results: Statistical analysis showed two distinct groups in terms of their perception of risk. The first group is represented by members with a high perception of risk and the second one with low risk perception. Finally, it is showed that educational level was only a significant variable for perceived risk explaining. Conclusions: Results are discussed in terms of existing literature concluding that training workers is necessary to raise their perception of risk.